Authentic Leadership and Its Role in Achieving Strategic Involvement An Analytical Exploratory Study of The Opinions of a Sample of Managers of the Mobile Communications Company in Iraq, Asia Cell - Abbas Obaid Edam, Haider; Abdullah Amana, Ahmed; Abbas Abboud, Rasha (Iraqi Journal for Administrative Sciences, 2024)
The aim of the research is to identify the extent of the impact of authentic leadership behaviors in achieving strategic Involvement in the branches of the (Asia Cell) mobile communications company in Iraq. The importance of the study is highlighted by examining and measuring the relationship and its impact between the study variables. For the purposes of analysis and statistical processing, a set of appropriate statistical methods were used. Such as the normal distribution test and confirmatory factor analysis. These methods were used through statistical programs (SPSS V.25; Amos V.25) The research community was represented by managers in all branches of Asia Waseel Company, and the size of the purposive sample was (167) individuals. and a set of conclusions were reached, the most important of which is the interest and efforts of the managements of the branches of the company in the study community in applying and adopting the dimensions of authentic leadership at the level. field, achieving strategic immersion. This study came up with a set of recommendations, the most important of which is the need to enhance authentic leadership behaviors in the researched company.